ARE CHILDREN WITH PETS AT GREATER RISK OF BEING COLONIZED BY STAPHYLOCOCCI? - A PRELIMINARY REPORT - M. Miszczak; P. Prorok; A. Korzeniowska-Kowal; A. Wzorek; A. Gamian; L. Szenborn; K. Rypuła; K. Bierowiec (International Journal of Infectious Diseases, 2023)
Intro: It is known that both coagulase-positive (CoPS) and coagulase- negative (CoNS) staphylococci can pose a real threat to human health, especially for young and immunocompromised patients. The present study reports impact of pet ownership on prevalence of the staphylococci in children. Methods: The study was conducted between 2019 – 2021. Samples (swabs from nares, oral cavity, skin behind the ear and in the elbow flexure) were collected from children with pets (n=24) and those without pets (n=12). Species identification was conducted using MALDI-TOF MS. Methicillin resistance (disc diffusion method, MIC, the presence of mecA and mecC genes) was determined for CoPS strains. Findings: Around 88.9% children carried any of Staphylococcus species. A greater number of different staphylococci species was observed in children who had animals in their home, but this observation was not statistically significant (p=0.0608). The most frequently isolated were S. epidermidis (70.8%; Cl 95%), S. aureus (50.00%; Cl 95%), S. lugdunensis (12.5%; Cl 95%) in children having a pet, while S. epidermidis (66.67%; Cl 95%), S. aureus (25.00%; Cl 95%) and S. hominis (16.67%; Cl 95%) were the most frequently isolated in children who had no pets. Methicillin resistant CoPS strains were detected in children with pets only. Any of the investigated Staphylococcus species was statistically more frequently isolated from children with close contact with pets. Conclusion: Staphylococci are common bacteria in children, regardless of animal exposure in the household. Some Staphylococcus species were more often isolated from children with pet contact (S. aureus; S. epidermidis, S. lugdunensis) and in some cases only from children with pets (S. pseudintermedius). The study should be extended to a larger study group to investigate further impact of animal contact on staphylococcal colonization in children.